A “fórmula da emoção” na fotografia de guerra: como as imagens de conflitos se relacionam com a tradição iconográfica explorada por Aby Warburg - Serva, Leão Pinto (2017)
This research seeks to identify the element responsible for the attractiveness of war photography, considering that conflict scenes are responsible for increasing audience of the media. The hypothesis of the research is that they contain Pathosformeln ("pathos formulas" or "passion formulas", concept created by the German critic Aby Warburg, 1866-1929), which cause impact by the immediate recognition of the emotions of the characters portrayed. Warburg pointed to the presence of ancient images from Pagan (Greek or Roman) culture appropriated by Renaissance artists and used as precoined forms for elements of expression of sentiment in paintings and sculptures from after the Middle Ages on. Since his death, the disciples of the German thinker have kept him as a reference to the study of ancient or Renaissance cultural manifestations, with rare exceptions (such as Carlo Ginzburg and Pablo Schneider, who use their concepts in analyzes of contemporary images). This research, which is linked to studies and reflections on Norval Baitello Jr.'s "Image Theory", applies to the War Photography, as a method, Warburg's analyzes of classical works, breaking his containment on ancient subjects. The chosen corpus is formed by photographs that obtained repercussion and recognition, participants of anthologies of this genre. The work, innovative as to the composition of the applied method and its object, detected in the analysis of the images several “formulas of emotion” used as paradigms in photos of conflicts